Inverted metamorphism and the main central thrust: field relations and thermobarometric constraints from the Kishtwar Window, NW Indian Himalaya - Stephenson, B; Waters, D; Searle, M (2000)
Following the early Eocene collision of the Indian and Asian plates, intracontinental subduction occurred along the Main Central Thrust (MCT) zone in the High Himalaya. In the Kishtwar-Zanskar Himalaya, the MCT is a 2 km thick shear zone of high strain, distributed ductile deformation which emplaces the amphibolite facies High Himalayan Crystalline (HHC) unit south-westwards over the lower greenschist facies Lesser Himalaya. An inverted metamorphic field gradient, mapped from the first appearance of garnet, staurolite and kyanite index minerals, is coincident with the high strain zone. Petrography and garnet zoning profiles indicate that rocks in the lower MCT zone preserve a prograde assemblage, whereas rocks in the HHC unit show retrograde equilibration. Thermobarometric results derived using THERMOCALC indicate a P-T increase of c. 180 °C and c. 400 MPa across the base of the MCT zone which is a consequence of the syn- to postmetamorphic juxtaposition of M1 kyanite grade rocks of the HHC unit on a cooling path over biotite grade footwall rocks, which subsequently attain their peak (M2) during thrusting. Inclusion thermobarometry from the lower MCT zone reveals that M2 was accompanied by loading, and peak conditions of 537 ± 38 °C and 860 ± 120 MPa were attained. M1 kyanite assemblages in the HHC unit, which have not been overprinted by M2 fibrolitic sillimanite, were not significantly affected by M2, and conditions of equilibration are estimated as 742 ± 53 °C and 960 ± 180 MPa. There is no evidence for dissipative or downward conductive heating in the MCT zone. Instead, the primary control on the distribution of peak assemblages, represented by the index minerals, is postmetamorphic ductile thrusting in a downward propagating shear zone. Polymetamorphism and diachroneity of equilibration are also important controls on the thermal profile through the MCT zone and HHC unit.